ISOLASI ASAM-9Z,12Z,15Z-OKTADEKATRIENOAT DARI BIJI SELASIH (Ocimum basilicum) - Fasya, Ahmad Ghanaim; Retnowati, Rurini; Rahman, M.; Duengo, Suleman; Warsito, Warsito (ALCHEMY, 2012)
The α-linolenic acid (9,12,15-octadecatrieonic acid) is omega-3 fatty acid that more active than other fatty acids to inhibit cell membrane damages, formation and growth of brain functions, antiinflamatory and prevent several cronic deseases like lung desease and arthrytis. Some research explain that geometri of omega-3 fatty acids had effect on its bioactivity. This research purpose was to isolate α-linolenic acid with geometry Z,Z,Z (9Z,12Z,15Z-oktadekatrienoat).O. basilicum seeds oil was isolated from O. basilicum seeds using Soxhlet extraction with n-hexane, then hidrolized by 12 % solution of KOH in aquadest. The α-linolenic acid was separated from other fatty acids by urea inclusion methods. The optimum condition of urea inclusion was determined in various temperature     (+ 5, + 3, + 1, + (-1), + (-3), + (-5))0C and ratio of fatty acid : urea 1:1; 1:1,5; 1:2; 1:2,5; 1:3; 1:3,5; 1:4.From this research, extraction of O. basilicum seeds oil with n-hexane as solvent resulted clear yellow-brown oil with refractive indeks 1,466 and density 0,855 g/mL. Gas Chromatography (GC) analysis of fatty acids hidrolyzed from   O. basilicum oil showed peak at tR= 19,949 minutes with relative percentage 70,72 %. Base on Mass Spectrum (MS), the fragmentation of this compound, with  tR= 19,949 minutes, was identic with 9Z,12Z,15Z-oktadecatrienoic acid.Isolation of α-linolenic acid from other fatty acids using urea inclusion at temperature 0-2 0C dan rasio fatty acid: urea 1:1,5 showed nonadduct fraction contains compound with tR= 19,980 minutes and relative percentage 88,51 %. Base on Mass Spectrum (MS), the fragmentation of this compound, with tR= 19,980 minutes, was identic with 9Z,12Z,15Z-oktadecatrienoic acid.